Dental Mesenchymal Stem Cell: Its role in tooth development, types, surface antigens and differentiation potential - Feter, Yohanna; Afiana, Nadhia Sari; Chandra, Jessica Nathalia; Abdullah, Kharima; Shafira, Jasmine; Sandra, Ferry (Molecular and Cellular Biomedical Sciences, 2017)
Reciprocal interaction between oral ectodermal epithelial cells and mesenchymal stem cells (MSCs)-derived from the cranial neural crest starts the teeth development. The role of dental MSCs continues throughout life. The dental MSCs do not only play a role in tooth development but also in tooth homeostasis and repair. There are many kinds of dental MSCs, such as dental pulp stem cell (DPSC), stem cell from apical papilla (SCAP), stem cell from exfoliated deciduous teeth (SHED), periodontal ligament stem cell (PDLSC) and stem cell from dental follicle (DFSC). Aligned with the proposed criteria by the International Society for Cellular Therapy (ISCT), dental MSCs are adherent cells and like other MSCs, dental tissue MSCs are capable of giving rise to cell lineages such as osteo/odontogenic, adipogenic, and neurogenic. Various surface antigens of dental MSCs were reported, however, mostly typical antigens suggested by ISCT were fulfilled. Surface antigens from each dental MSCs (DPSC, SCAP, SHED, PDLSC and DFSC) are being described in the current report.Keywords: dental stem cells, mesenchymal stem cells, tissue regeneration, DPSC, SCAP, SHED, PDLSC, DFSC